Finite Element Analysis of Composite Pressure Vessel Using Reduced Models - Jadoon, Junaid; Shazad, Atif; Muzamil, Muhammad; Akhtar, Maaz; Sattar, Mohsin (TECCIENCIA, 2022)
Pressure vessels are one of the essential industrial tools for high-pressure containments. Catastrophic failure of pressure vessels is detrimental to society. It is essential to design pressure vessels by selecting high-strength materials and analyzing them beyond working loads to ensure safety. Liner less composite cylinders have gained importance in the pressure vessel industry owing to their high strength-to-weight ratios, corrosion resistance, etc. However accurate and efficient prediction of their mechanical properties was required. Finite element methods were employed for the structural analysis of reduced models. The three-dimensional shell structure of the Graphite/Epoxy composite system was analyzed using APDL. Appropriate boundary conditions were applied to 5x reduced models internally pressurized to 20 MPa. Suitable mesh size was selected through mesh independence and stress distributions were discussed for reduced models, especially for the inner two layers. Comparison with previous research confirmed the validity of models. 0.1° rotated strip of vessel gives accurate and conservative results. Tsai Wu, Tsai Hill, Maximum Shear Stress (Smax), and Von Mises were used to assess the failure of composite cylinders. Each of the failure criterion predicts the failure of the second layer for all the reduced models.